Radon Concentration Measurement Indoors and Outdoors - AlFakhar , Mohammed Kassim; Ikraiam, Fawzi Abdulkariem (Al-Mukhtar Journal of Sciences, 2001)
In this research, the passive integrated dosimeter technique with solid state nuclear track detectors, super grade CR-39, was used to measure the concentration of the radioactive radon gas (Rn222) indoor and outdoor for six different positions. For this purpose, the etching optimal conditions for CR-39 were studied. Etching conditions are controlled by three principal variables. These variables are etching solution temperature, morality and etching time. To measure radon concentration, 270 detectors were prepared and were distributed in the chosen positions. After 100 days, the detectors were collected and treated chemically by using the above conditions. Then the number of tracks per unit area in 20 sites in each detector were measured by an optical microscope. Results obtained showed that radon concentration indoors was (6.3 pci/L) while outdoors was (0.3 pci/L). These results indicate that the risk factor of lung cancer for residents of this region due to radon R222 increases by 1.2%.